Strategies of Massacres, Coup Strategies and Trial Strategies. Some Analyses on the Memory of the Piazza Della Loggia Massacre and the Subversive Strategies and Concealment of the Truth in Italian History in the Sixties and Seventies of the Past Century (Italian Review of Legal History, 2024)
Remembering the tragedy of Piazza della Loggia in Brescia according to the guidelines of the conference Stragi e strategie. Questioni di giustizia verità e memoria led to retrace the key episodes of ten years of Italian history: years devastated by the attempts to overthrow the principles of the democratic constitution. The strategies of the subversive right groups were carefully planned to instill terror and disorientation in citizens. From an ideological and political point of view, the elimination of the principle of the balance of powers was pursued with three attempted coups d’état aimed at establishing authoritarian governments. In addition to the determination to further weaken the judiciary and eliminate the «red judges», there were also ‘deviations’ to prevent or alter the investigations into those responsible, instigators and executors, of the massacre so that it was impossible to fully ascertain the judicial and historical truth. All these aspects can be traced in the «procedural tangle» that has still not allowed complete justice to be done, fifty years after the tragic 28 May 1974, five phases of investigation and thirteen trials.
Keywords: History of Italy 1964-1974; massacres; coup d’état; secret services; criminal trial; judiciary; guarantees; ascertainment of the truth